Income Assistance, Marriage, and Child Poverty: An Assessment of the Family Security Act - Salvador Ortigueira; Nawid Siassi (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2021)
The Covid-19 pandemic has brought about changes in key income support programs, reigniting a debate about the design of financial aid to low-income households with children. In this study we assess the Family Security Act - a proposal presented by Senator Mitt Romney (R-UT) on February 4, 2021 to reform the tax/transfer system-in terms of its efficacy to achieve the stated objectives of increasing marriage rates and cutting child poverty at no cost to the government. The assessment is carried out through a structural microsimulation approach, using a dynamic model of savings, labor supply, household formation, and marital status. We find that while the plan would be highly effective at increasing marriage, it would reduce child poverty at the expense of increasing poverty among single-mother families and child deep poverty. Furthermore, the plan would entail a substantial cost to taxpayers.
Keywords: E21; H24; H31; J12; 330; Income Support; household decisions; cohabitation and marriage; poverty